STRATEGI PEMASARAN PT SAYURAN SIAP SAJI KABUPATEN BOGOR JAWA BARAT - Dhia Andarifika Kasymir; Dwi Haryono; Rio Tedi Prayitno (Lampung University, 2019)
This research aimed to formulate the Marketing Strategy of PT Sayuran Siap Saji Bogor Regency of West Java. This research used a case study method at PT Sayuran Siap Saji of Sukamanah Village, Megamendung District, Bogor Regency, West Java. The samples were GA-HRD, distribution marketing manager of the company, two employees of the marketing division (distribution), one of costomer of the highest number of purchases, and the ex-customer. The data was analyzed by descriptive analysis, SWOT analysis and QSPM. The results of this research showed that for strategies combination value IFE was 2,96 and value of EFE was 2.29 in the IE matrix shows that the position the business in quadran V. It meant that the company was in the growth area. On QSPM it was known that the marketing strategy of PT Sayuran Siap Saji was to maintain and improve product quality in order to excel in trading, improved the company's marketing management and optimize product publication in order to increase consumer interest, wider promotion and partner with new supplier, products to be more competitive in the market.Key words: marketing strategy, QSPM, Sayuran Siap Saji